EMPHASIS OF TECHNOLOGY IN ENGLISH CLASSROOM - Buriev Dilmurod Arzimurodovich (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article is to study technologies as a part of methods, its some categories and its formation in the English languages.